The Role of Local Wisdom in Disaster Mitigation: A Systematic Literature Review (SLR) Approach - Syuryansyah, Syuryansyah; Habibi, Fikri (TDMRC, Universitas Syiah Kuala, 2023)
This research analyzes the role and implementation of local wisdom in disaster management in Indonesia. The study focuses on the three stages of disaster management: pre-disaster, during the disaster, and post-disaster. The approach of